How internal factors determine digital transformation: The moderating role of leader's project management competence - Man Do Thi; Tra Dao Thu (Journal of Project Management)
Digital transformation refers to technological application with a comprehensive shift in corporate governance's mindset, structure, and strategy. In particular, digital transformation project management is key in ensuring that digital transformation initiatives are implemented on schedule and achieve the set goals. This study investigates the importance of a leader's project management competence and other internal factors in successfully implementing digital transformation projects. Through Partial Least Squares Structural Equation Modeling (PLS-SEM), data collected from questionnaires administered to 436 small and medium-sized enterprises (SMEs) in Thanh Hoa, Vietnam shows that all four internal factors included in the model directly affect the transform digital ability and indirectly affects the level of digital transformation of SMEs, in which the most decisive influence comes from digital transformation strategy, followed by the influence of corporate culture, technology platform and finally workforce competence. More specifically, this study has demonstrated that an enterprise's digital transformation can be considered a project, and the leader's project management competence determines the project's success. The project management capacity of the enterprise leaders not only directly affects the digital transformation results but also plays a positive moderator in the association between digital transformation capability and the digital transformation level of SMEs. The results suggest several recommendations for leaders of SMEs in Thanh Hoa Province to improve project management capacity, thereby promoting the digital transformation process.